The establishment of PD-1 inhibitor treatment prognosis model based on dynamic changes of peripheral blood indexes in patients with advanced lung squamous cell carcinoma - Xie, Yuyan; Sun, Hao; Shan, Liying; Ma, Xin; Sun, Qingyu; Liu, Fang (Frontiers in Oncology, 2024)
BackgroundUnlike patients with lung adenocarcinoma, patients with lung squamous cell carcinoma (LUSC) do not derive significant benefits from targeted therapy. In recent years, immunotherapy has revolutionized the treatment approach for LUSC. However, not all patients with this type of cancer respond to immunotherapy, necessitating the identification of effective biomarkers to predict survival prognosis and evaluate the efficacy of PD-1 inhibitors.Materials and methodsWe retrospectively collected case and hematologic data from 212 patients with advanced squamous lung cancer who received PD-1 combination therapy. Hematological indices mainly contained SCC, CEA, NSE, Hb, LDH, WBC and RBC at baseline, 6 and 12 weeks of treatment. All patients underwent imaging examinations and efficacy was evaluated according to RECIST1.1 criteria. Univariate tests were used to assess the relationship between changes in serum biomarkers, clinical characteristics and treatment outcome. The survival prognosis of patients was investigated by telephone follow-up. The optimal critical values of all hematological indicators were calculated by ROC curves, and then logistic regression and Cox regression were used to analyze multiple serum markers in relation to efficacy and survival prognosis, respectively. Finally, column line plots were constructed and validated to predict the probability of patient survival.ResultsPost-treatment RBC12w<3.81 × 10 12/L (p < 0.034) was associated with lower ORR, and WBC6w<9.34 × 109/L (p=0.041) was associated with higher DCR.SCC12w≥2.25 ng/mL (p = 0.015), NSE6w≥13.54 ng/mL(p = 0.044)and RBC0w≥4.2 × 10 9/L (p = 0.003) were independent predictors of PFS. SCC12w≥2.25 ng/mL (p < 0.001) and NSE6w≥13.54ng/mL(p = 0.042) were independent predictor of OS. Patients in the SCC12w≥2.25 ng/mL (HR = 1.943,95% CI:1.218-3.079 vs. HR = 2.161,95%CI:1.087-3.241) and NSE6w≥13.54 ng/mL (HR = 1.657,95% CI:1.118-2.535 vs. HR = 2.064,95% CI:1.569-4.169) groups had shorter PFS and OS. In subgroup analysis, patients with stage III advanced squamous lung cancer had a better pro-gnosis than those with stage IV. PD-L1-positive, and SCC12w ≥2.25 ng/mL had a worse prognosis. The results of constructing column-line plots for predicting the survival probability of 1-, 3-, and 5-year PFS and OS: The C-index and 95% CI for PFS and OS of column-line plots were 0.725 (95% CI: 0.478-1.928) and 0.755 (95% CI: 0.642-0.868), respectively, and the bootstrap correction showed a good consistency of the column-line plots.ConclusionChanges in RBC12w ≥3.81×1012/L, WBC6w ≥9.34×10 9/L, SCC12w ≥2.25 ng/mL, and NSE6w ≥13.54 ng/mL after treatment are prognostic indicators of immunotherapy in patients with advanced squamous lung cancer.